The prognosis of mild cognitive impairment: A systematic review and meta‐analysis - Simone Salemme; Flavia Lucia Lombardo; Eleonora Lacorte; Francesco Sciancalepore; Giulia Remoli; Ilaria Bacigalupo; Paola Piscopo; Giovanna Zamboni; Paolo Maria Rossini; Stefano Francesco Cappa; Daniela Perani; Patrizia Spadin; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Knowledge gaps remain about the prognosis of mild cognitive impairment (MCI). Conversion rates to dementia vary widely, and reversion to normal cognition has gained attention. This review updates evidence on MCI conversion risk and probability of stability and reversion. METHODS We searched databases for studies on MCI prognosis with ≥3 years of follow‐up, established criteria for MCI and dementia, and performed a meta‐analysis using a random‐effects model to assess conversion risk, reversion, and stability probability. Meta‐regressions identified sources of heterogeneity and guided subgroup analysis. RESULTS From 89 studies (mean follow‐up: 5.2 years), conversion risk was 41.5% (38.3%–44.7%) in clinical and 27.0% (22.0%–32.0%) in population‐based studies, with Alzheimer's dementia as the most common outcome. Stability rates were 49.3% (clinical) and 49.8% (population). Reversion was 8.7% (clinical) and 28.2% (population). DISCUSSION Our findings highlight higher conversion in clinical settings and 30% reversion in population studies, calling for sustainable care pathway development. Highlights Prognosis for mild cognitive impairment (MCI) varies by setting; dementia risk is higher and the probability of reversion is lower in clinical‐based studies. In both clinical and population settings, cognitive stability is ≈50%. A reorganization of health services could ensure sustainable care for individuals with MCI. Significant heterogeneity in MCI studies impacts data interpretation; follow‐up length is crucial. Long‐term prognosis studies on MCI in low‐ and middle‐income countries are urgently needed.